Increasing The Ability And Adoption Of Goat Breeding Technology In Mitra Sepakat Farmer Group Kabupaten Sijunjung: Peningkatan Kemampuan Dan Adopsi Teknologi Beternak Kambing Pada Kelompok Tani Mitra Sepakat Kabupaten Sijunjung - Rini Elisia; Maiyontoni; Afrini Dona; Fadilla Meidita; Refika Komal; Taufiqqurrahman (Journal of Community Service and Application of Science, 2022)
Goat rearing in Kenagarian Palaluar Kecamatan Koto VII Kabupaten Sijunjung is carried out extensively with field grass feed. This causes the potency of goat kacang is not optimal. There are no practical and health-qualified livestock cages, forage cultivation gardens, feed preservation, handling of sick livestock, or untapped livestock waste to reduce pollution. If the potential of kacang goat farming can be optimized, it can improve the economy of farmers. The purpose of this activity is to improve the ability of goat farming Mitra Sepakat farmer group through the adoption of technology and goat farming management. This activity began in 2020 starting with: the selection and cultivation of forage animal feed, demonstration plots of effective goat cages and selection breed goats; in 2021, feed management, fermentation feed manufacturing, concentrate manufacturing, reproduction management, and business analysis; in 2022, this was continued by the activity of making fermented feed, managing goat livestock waste into manure and evaluating the application of goat breeding science and technology that had been given. Based on the evaluation of the implementation of service activities that have been carried out from two years ago have been: a) changes in goat breeding patterns from (15 people) 100% extensive to 8 people (53) % intensive and intensive breeding patterns have been able to implement 100% transfer of Science and technology provided. The results of the evaluation conducted still found some problems faced by farmers such as the calf mortality rate being quite high, which became the plan for the next service for the next service activities.